Impact of biofeedback therapy on patients with fecal incontinence or constipation in a gastrointestinal neurophysiology unit in Bogotá, D.C. - Daza Castro, Mauricio (2024)
Introduction: Treatment of functional disorders of the anorectal unit should focus on the underlying cause. Biofeedback therapy is a functional retraining of the pelvic floor that has proven useful in the treatment of constipation associated with dyssynergia and in the management of fecal incontinence. This study describes the first experiences with this form of biofeedback therapy in Colombia. Objective: Describe our experience with biofeedback therapy in the gastrointestinal neurophysiology unit. Materials and methods: This historical cohort included patients with an indication for biofeedback therapy for constipation or fecal incontinence in the gastrointestinal neurophysiology unit during the data collection period. The response to therapy is described by comparing manometric findings before and after 10 biofeedback sessions. Results: 21 patients were included (71.4% women, the average age was 68, 9 with constipation and 12 with fecal incontinence. Among the patients with constipation there was a significant improvement in 71.4% of those who had rectal hyposensitivity and in 57.1% of those with dyssynergia. Biofeedback therapy significantly increased the balloon expulsion rate (11.1 vs. 66.7%, p=0.02). In patients with fecal incontinence, there was improvement in 50% of those who had anal hypotonia and in 80% of those who had anal hyposensitivity. Conclusions: This study demonstrates that biofeedback therapy has a favorable impact on a high number of patients with constipation and fecal incontinence; in our center, the response is similar to that of the world literature.